Spatial Structure Of Agricultural Biodiversity In Southern Mali - Dembele, Sidi; Soumare, Mamy; Gaillard, David (European Scientific Journal, ESJ, 2016)
The diversity of cropping systems and varieties plays an important role in the ability of family farms to resist socio-economic and environmental shocks. For better conservation, agricultural diversity needs to be characterized and monitored in space and time. While initially dominated by the elements on price, surfaces, and productions, agricultural monitoring systems have recently incorporated diversity issues. The objective of this work is to analyze the spatial structure of agricultural biodiversity and to explain the links between this structure and the agronomic practices and results in family farms in southern Mali. The methodology was to develop, test, and maintain a conceptual model of spatial data on a sample of three villages. The analysis of these data is based on the spatial distribution of biodiversity and its correlation with the practices and agro-ecological conditions, results, and agronomic performance. The results show a very large specific and varietal diversity. We do not observe a clear link between spatial distribution and the characteristics of the physical environment, with the exception of the improved variety of Kalafoufigue located on a particular type of slope. The same observation is made when the relationship is between the spatial distribution of the variety and the technical route. Spatial analysis has developed a map of the diversity across the country village. Thus, spatial distribution points plot a surface distribution across local villages, and these results open the way for greater contributions of geographical analysis in agriculture and for scaling territories that remain a challenge for agriculture.